Type II caesarean scar pregnancy management by ultrasound-guided local lauromacrogol injection in combination with suction curettage: A case report. Issue 17 (April 2020) - Wei, Shuang-shuang; Li, Ding-heng; Zhang, Zhi-fen; Sun, Wen-chao; Jia, Cen-lin
Abstract: Introduction: The implantation of a gestational sac within the scar of a previous caesarean delivery is defined as caesarean scar pregnancy (CSP), which is classified into two types: CSP I and CSP II. CSP II is life threatening, and no clear consensus for CSP II management exists. Patient concerns: A 31-year-old woman, gravida 1, para 1, with a previous caesarean delivery due to macrosomia, presented with an estimated 45 days of amenorrhea. The patient presented to the emergency department with vaginal bleeding for 1 day and no abdominal pain. Diagnoses: An ultrasound examination was performed demonstrating a viable fetus that was embedded in the caesarean scar area and was bulging through the wall of the uterus into the bladder without contact with the uterine cavity or cervical canal. A diagnosis of type II caesarean scar pregnancy was made. Interventions: Local lauromacrogol was used to reduce the gestational sac blood supply. Suction curettage was performed under the guidance of abdominal ultrasound 24 h later, and the amount of bleeding was 20 mL. The response to the treatment was monitored by serial beta-human chorionic gonadotropin (β-hCG). Outcomes: Patient was followed up with β-hCG weekly levels which became <10 mIU/mL after 4 weeks of treatment. Conclusion: Ultrasound-guided local lauromacrogol injection combined with suction curettage may be a safer and novel therapeutic method. Abstract : Supplemental Digital Content is available in the text